Effect of the surroundings on the photophysical properties of CsPbBr3 perovskite quantum dots embedded in SiOx matrices. (27th September 2022) - Lee, Soo Jeong; Lee, You Jeong; Seo, Sumi; Jo, Hyeonyeong; Han, Donghoon; Yoon, Seog Joon
Abstract: Organometallic lead halide perovskites have been studied extensively owing to their excellent photophysical properties and have been successfully applied to solar‐driven chemistry and optoelectronic devices. Dimensionally confined perovskite quantum dots (PQDs) have demonstrated outstanding photoluminescence quantum yields, detailed band gap tunability, wide color gamut, and favorable radiative recombination processes. These characteristics expand the versatility of PQDs. Various efforts have been made to increase their stability. The introduction of a core–shell structure increased the stability of PQDs, and they were successfully applied to light‐emitting diodes. Recently, our group demonstrated the potential of PQDs to promote photocatalytic degradation of carcinogens. However, further studies on the detailed interactions between PQDs and their surroundings are necessary to utilize them in practice. This study investigated the impact of surrounding solvents on the material/photophysical properties of PQDs and statistically observed the photoinduced charge transfer from PQDs to transparent conducting oxides. The findings of this study could be used to advance solar‐driven chemistry and optoelectronic devices and to promote the utilization of PQDs in renewable energy applications. Abstract : We present the impact of the surroundings on the material/photophysical properties of CsPbBr3 @SiOx perovskite quantum dots (PQDs) and statistically observed the photoinduced charge transfer from PQDs to transparent electrodes.